0373 Pooling case-control studies for enhanced evidence on occupational risk factors in lung cancer research – the SYNERGY project. (23rd June 2014) - Olsson, Ann; Kromhout, Hans; Vermeulen, Roel; Peters, Susan; Pesch, Beate; Behrens, Thomas; Kendzia, Benjamin; Schüz, Joachim; Straif, Kurt
Abstract : Objectives: Explore quantitative exposure-response association for exposure to asbestos, crystalline silica, nickel, chromium and polycyclic aromatic hydrocarbons in the general population; further study effects on specific cell types and potential interaction with smoking and co-occurring occupational exposures. Method: Fourteen studies from Europe and Canada were pooled including 17 700 lung cancer cases and 21 800 controls with detailed information on tobacco habits and lifetime occupations. A quantitative job-exposure-matrix (SYN-JEM) was developed based on more than 350.000 exposure measurements from the participating countries. Different model specifications were compared to predict historical job-, time-, and region-specific exposure levels. Individual exposure levels were calculated for each subject by linking the SYN-JEM with the individual occupational histories. Unconditional logistic regression models were fitted to estimate odds ratios, 95% confidence intervals, and trends. Results: We observed exposure-response relationships with increasing duration and cumulative exposure for all agents and generally saw a stronger effect for squamous- and small cell lung carcinomas than for adenocarcinomas. Smoking and simultaneous exposure to other occupational exposures exerted a minor confounding effect on the risk estimates. The effect modifications with smoking tended to be supra-additive. Conclusions: SYNERGY adds valuable knowledge to the field of occupational cancer epidemiology, and underlines the importance to collect data on histology, and lifelong information on occupational exposures and smoking.